Lire et être lu. Littérature et catastrophe dans le Journal d’Hélène Berr - Zoé Egelman (Conserveries Mémorielles)
Little scholarship on Hélène Berr’s Journal has surfaced since its publication in France in 2008. Indeed, Berr’s voice stands on its own; her eloquence leaves little room for commentary. The aim of this paper is to shed light on a central motif of the diary and demonstrate how it necessarily shapes Berr’s experience of the Paris Occupation: the role of literature and how its function evolves from the first to last sentence of the text. This paper is the first to simultaneously and closely examine: Berr’s archival record, including papers from the Centre de documentation juive contemporaine and the Archives nationales; the novels, poems, narratives, and theater that Berr read from 1942 to 1944; and, of course, the language of the diary itself. Reading the texts in Berr’s bookshelf alongside the diary deepens the impact of Berr’s testimony by illuminating some of Berr’s most complex thoughts and transforms the meaning of literary works in the context of the Occupation and Jewish persecution in Paris. This study ultimately addresses a number of historical and literary issues, from the awareness in Paris of Jewish persecution, to apocalyptical literature during a time of disaster.